Indirect taxation in developing economies : the role and structure of customs duties, excises, and sales taxes - Due, John F. (Baltimore : London : Johns Hopkins Press, 1970)
The volume draws upon value-added taxation in a variety of countries including Venezuela, Honduras, Chile, El Salvador, Zambia, the other British Commonwealth countries in Africa, and the Philippines, as well as work in the United States and Canada.
Includes bibliographical references and index.
ne 22/01/2019
Loans
Keywords: Indirect taxation